2019
DOI: 10.1136/bmjgh-2018-001232
|View full text |Cite
|
Sign up to set email alerts
|

Automated phone call and text reminders for childhood immunisations (PRIMM): a randomised controlled trial in Nigeria

Abstract: BackgroundSub-Saharan Africa has high under-5 mortality and low childhood immunisation rates. Vaccine-preventable diseases cause one-third of under-5 deaths. Text messaging reminders improve immunisation completion in urban but not rural settings in sub-Saharan Africa. Low adult literacy may account for this difference. The feasibility and impact of combined automated voice and text reminders on immunisation completion in rural sub-Saharan Africa is unknown.MethodsWe randomised parturient women at the Mother a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 15 publications
4
42
0
Order By: Relevance
“…The full vaccination coverage at 12 months in both the intervention and usual care groups was lower than the national targets, indicating the importance of additional interventions to strengthen the immunization program. Our findings were consistent with those reported in studies from Bangladesh [ 66 ], Nigeria [ 68 ], and Côte d'Ivoire [ 71 ], which reported that SMS text reminders improved childhood vaccination coverage. Our findings were also in line with those of other studies that observed that mobile phone–based reminders significantly improved attendance to different health service appointments [ 61 , 75 , 99 - 101 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The full vaccination coverage at 12 months in both the intervention and usual care groups was lower than the national targets, indicating the importance of additional interventions to strengthen the immunization program. Our findings were consistent with those reported in studies from Bangladesh [ 66 ], Nigeria [ 68 ], and Côte d'Ivoire [ 71 ], which reported that SMS text reminders improved childhood vaccination coverage. Our findings were also in line with those of other studies that observed that mobile phone–based reminders significantly improved attendance to different health service appointments [ 61 , 75 , 99 - 101 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in line with that of other studies conducted in Zimbabwe [ 44 ], Kenya [ 43 ], and the United States of America [ 102 , 103 ]. However, randomized clinical trials conducted in the United States of America [ 73 ], Guatemala [ 74 ], Pakistan [ 70 ], and Nigeria [ 68 ] observed a higher vaccination coverage for specific vaccines attributable to text message reminders, which are not statistically significant at 5% significance level. The differences in the effect of the text message reminders could be related to the way text messages had been developed and delivered to the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…15 Mobile health (mHealth) interventions have been used to provide health information on vaccines, as well as send alerts and reminders to beneficiaries to improve immunisation timeliness. 16 Programmes in Zimbabwe, 17 Kenya, 18 Nigeria 19 and Bangladesh, 20 which have used vaccination appointment reminders and immunisation-related prerecorded messages, have been found to positively influence immunisation uptake. But, in rural Haryana, India, a text message service, which sent reminders to care-givers and used Global Positioning Satellites to track children who had missed appointments was found to have no significant impact on full and timely vaccination of children.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Most studies (n=4689) were excluded. After eligibility and critical appraisal of the full texts of 39 records, 18 studies met the inclusion criteria for data extraction, qualitative synthesis and meta-analysis, [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] while 21 studies were excluded for the following reasons: intervention was not SMS reminder (n=9), [64][65][66][67][68][69][70][71][72] study setting was not an LMIC (n=2), 73 74 conference abstract (n=2), 75 76 literature reviews (n=2), 77 78 could not extract data on specific effect of SMS reminder (n=2), 79 80 observational case-control study (n=1), 81 no comparator/control arm (n=1), 82 control arm not usual care (n=1) 83 and outcome was not DPT-3, Penta-3 or overall immunisation (n=1). 84 Characteristics of included studies Table 1 summarises the main characteristics of the 18 studies included in the analysis.…”
Section: Selection Of Studiesmentioning
confidence: 99%